A solid electrolyte lithium aluminum titanium phosphate precursor and its preparation method and application

Ultrafine titanium aluminum lithium precursors are prepared through hydrothermal reactions of titanium source, aluminum source and phosphoric acid, which solves the problem of nano titanium aluminum phosphate preparation in the prior art, and achieves uniform control of particle size and safe and environmentally friendly production , improves the performance of the positive electrode material.

CN118637585BActive Publication Date: 2024-12-13SUZHOU GUTAI TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411096174.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-12
Publication Date
2024-12-13
Estimated Expiration
2044-08-12

AI Technical Summary

Technical Problem

The prior art is difficult to prepare nano-titanium aluminum-aluminum-phosphate materials less than 100 nm, and the commonly used methods have problems such as flammable and explosive organic solvents, ammonia nitrogen wastewater discharge, high production costs, safety and environmental protection, and it is difficult to achieve uniform control and dispersion of particle size. sex.

Method used

Hydrothermal reaction is carried out using titanium source, aluminum source and phosphoric acid to form a semi-solid gel, and hydrothermal treatment is carried out in combination with lithium source to obtain ultrafine titanium aluminum lithium precursor with good crystallinity, avoid the use of organic solvents and ammonia nitrogen, and realize particles The size is controlled at 5~30 nm and nanotitanium aluminum phosphate is formed by simple calcination.

Benefits of technology

The preparation of titanium aluminum lithium phosphate precursor with small particle size and uniform size distribution is realized, the process is simplified, production costs are reduced, safe and environmentally friendly, and the circulation stability and coating effect of the positive electrode material are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118637585B_ABST
    Figure CN118637585B_ABST
Patent Text Reader

Abstract

The present invention provides a solid electrolyte lithium titanium aluminum phosphate precursor and a preparation method and application thereof, wherein the solid electrolyte lithium titanium aluminum phosphate precursor comprises lithium, aluminum, titanium, oxygen, hydrogen and phosphorus; in the XRD spectrum of the solid electrolyte lithium titanium aluminum phosphate precursor, the peak intensity ratio of the first strong diffraction peak and the second strong diffraction peak is 0.5-2.0, and the half-height width range of the first strong diffraction peak and the second strong diffraction peak is independently 0.3-0.8°; the peak position of the first strong diffraction peak is within the range of 26.5-27.5°, and the peak position of the second strong diffraction peak is within the range of 27.5-28.5°. The present invention can obtain lithium titanium aluminum phosphate precursor particles with a primary particle size of 5-30nm, and the precursor can be directly used for surface coating of positive electrode materials, and the precursor particles only need simple calcination to be converted into nano lithium titanium aluminum phosphate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of batteries and relates to a solid electrolyte lithium titanium aluminum phosphate precursor and a preparation method and application thereof. Background Art

[0002] At present, mainstream liquid lithium-ion battery technology has bottlenecks in safety and energy density. Solid-state lithium-ion batteries are believed to be able to overcome the defects of liquid batteries. Solid electrolytes, as the basis and core material for the transformation of liquid lithium-ion batteries to solid / solid-liquid hybrid lithium-ion batteries, determine the development of solid-state lithium-ion batteries. Solid electrolytes used in lithium-ion batteries can be mainly divided into three categories: polymers, sulfides and oxides. In the oxide solid electrolyte system, the representative material of NASICON (sodium fast ion conductor) type is lithium aluminum titanium phosphate Li 1+x Al x Ti 2-x (PO4)3 (LATP, x=0-0.5) is one of the most promising lithium fast ion conductors due to its high room temperature ionic conductivity (close to the level of commercial organic electrolytes), wide electrochemical window, and high chemical and thermal stability.

[0003] For different applications, it is sometimes necessary to make the particle size of the solid electrolyte fine and uniform and controllable, such as positive electrode surface coating, ion-electronic composite conductive agent, etc. The methods for preparing LATP usually include high-temperature solid phase method, coprecipitation method and sol-gel method. These methods all require high-temperature calcination in the final stage to obtain the final product LATP, resulting in the prepared LATP particles being larger in size and agglomerating to varying degrees. It is necessary to obtain nano-sized (usually >100nm) LATP through mechanical ball milling or sand milling. However, the powder after ball milling or sand milling is also very easy to agglomerate, which hinders the industrialization process of LATP solid electrolyte. In addition, too long grinding reduces production efficiency, occupies grinding equipment, easily causes crystal defects in LATP particles, and introduces grinding medium impurities.

[0004] As mentioned in CN 111740167A: raw materials including titanium compounds, organic solvents, mixed solvents, lithium source compounds, aluminum source compounds and phosphorus source compounds are mixed to obtain a reaction precursor solution; the reaction precursor solution is heated to react to obtain a precipitate, and then the precipitate is heated, pre-decomposed and calcined to obtain a nano-lithium titanium aluminum phosphate solid electrolyte. This method can controllably prepare nano-lithium titanium aluminum phosphate solid electrolytes with a size in the range of 20-100nm in large quantities, but it requires the use of an organic solvent to dissolve the titanium source, which is flammable, explosive and has organic waste. The problem of liquid discharge and high production cost; ammonia-containing substances are often used in the reaction process, which also causes difficulties in wastewater treatment. At the same time, its low-pressure solvothermal method synthesizes nano-titanium aluminum phosphate lithium solid electrolyte materials with a particle size distribution in the range of 20-100nm. There are doubts about whether the material has been calcined at 800℃ for 6h. The product synthesized by the low-pressure solvothermal method needs to be pre-decomposed by heating at a temperature of 500-800℃ for 2-6h and calcined at a temperature of 800-1100℃ for 6-12h to obtain.

[0005] For example, CN 114804052A discloses a titanium aluminum phosphate precursor material comprising aluminum, titanium, phosphorus and oxygen. The precursor material is prepared by a solid phase sintering method. The X-ray diffraction XRD pattern of the precursor material has characteristic diffraction peaks at 2θ angles of 22°, 25° and 27°. The precursor material does not contain the Li element, and a lithium source needs to be added during the subsequent calcination. At the same time, the high-temperature calcination at 1400°C consumes high energy, and the particle size of the obtained material particles is several or even more than ten microns, making it difficult to prepare small-particle lithium titanium aluminum phosphate materials.

[0006] For example, in CN 111233458A, an AlOOH precursor is first prepared by a liquid phase method, and then mixed with lithium salt, titanium salt and phosphate salt according to the target stoichiometric ratio, and then subjected to ball milling, pre-sintering and forming sintering to obtain a lithium aluminum titanium phosphate solid electrolyte material. The preparation precursor is a mixture, and the particle size of the lithium aluminum titanium phosphate material prepared thereby is >1µm.

[0007] For example, CN114914528A discloses a lithium titanium aluminum phosphate solid electrolyte and its preparation method and application, which uses cheap and readily available inorganic salts as raw materials to prepare high-quality lithium titanium aluminum phosphate materials. However, this solution uses a large amount of hydrogen peroxide and ammonia water, which poses safety and environmental protection problems, and fails to control the particle size of the lithium titanium aluminum phosphate.

[0008] For example, in CN 115458804A, raw materials are configured according to the stoichiometric ratio of lithium aluminum titanium phosphate to prepare a precipitate, and the precipitate is washed. Water is used as a solvent in the process of preparing the precipitate. The washed precipitate is added with water to form a suspension, which is then transferred into a sealed pressure vessel, reacted at a certain temperature for a period of time, and then the reacted material is dried to obtain a precursor powder; the precursor powder is subjected to heat treatment to obtain a solid electrolyte lithium aluminum titanium phosphate; however, it uses one or more of ammonium dihydrogen phosphate and diammonium hydrogen phosphate as a phosphorus source, involving the discharge of ammonia nitrogen wastewater, increasing the difficulty of wastewater treatment, and causing great pollution to the natural environment. A mixed salt solution containing an aluminum source, a titanium source, and a phosphorus source is neutralized with an alkaline solution to form a precipitate, which is then washed with water, which easily causes incomplete washing of impurity ions.

[0009] For example, CN 117525359A discloses a fast ion conductor coated high voltage and high specific capacity lithium cobalt oxide positive electrode and a preparation method thereof, wherein LATP is weighed and added to a beaker, deionized water is added, and the mixture is stirred in a constant temperature heated magnetic stirrer to disperse the LATP in the deionized water to form a hydrosol; a corresponding mass of high pressure lithium cobalt oxide powder is weighed and added to the LATP hydrosol, stirred to fully mix the mixture, and then heated to fully evaporate the deionized water therein by constant temperature stirring; the remaining mixed powder after evaporation is dried in an oven, fully ground in an agate mortar, and the mixed powder is transferred to a muffle furnace for sintering, heated, and naturally cooled before grinding again to obtain a final product; the surface of the lithium cobalt oxide positive electrode is coated with LATP, and the performance of the lithium ion battery using the LATP coated lithium cobalt oxide positive electrode is improved, but the liquid phase coating method used may be difficult to ensure the uniformity of the coating.

[0010] It can be seen that the primary particle size of nano-lithium titanium aluminum phosphate material is relatively large, and it is easy to agglomerate, which is not conducive to achieving thin and uniform surface coating or uniform mixing. In addition, most of the existing technologies use organic titanium sources, organic aluminum sources, and organic solvents as reactants, which are costly and flammable and explosive, and there are organic emissions during the reaction process, which are difficult to recycle and treat; in the scheme using inorganic salts as raw materials, a large amount of hydrogen peroxide and ammonia water will be used as raw materials, which is not conducive to environmental protection and safety, and it is difficult to prepare nano-lithium titanium aluminum phosphate materials less than 100nm in industrial amplification.

[0011] Based on the above research, the present invention provides a solid electrolyte lithium aluminum titanium phosphate precursor, which has a small particle size, uniform size distribution, is easy to disperse, and can form LATP after calcination. Therefore, it can be used as a coating material to replace LATP for coating the surface of the positive electrode material, which plays a positive role in improving the cycle stability of the positive electrode material. Summary of the invention

[0012] The purpose of the present invention is to provide a solid electrolyte lithium aluminum titanium phosphate precursor and a preparation method and application thereof. The solid electrolyte lithium aluminum titanium phosphate precursor has a specific strong diffraction peak, and the strong diffraction peak has a specific peak intensity ratio and half-height width. Because of its small particle size, uniform size distribution, and easy dispersion, LATP can be formed after calcination. Therefore, it can also be directly used as a coating material to replace LATP for coating the surface of a positive electrode material to improve the performance of the positive electrode material.

[0013] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:

[0014] In a first aspect, the present invention provides a solid electrolyte lithium titanium aluminum phosphate precursor, wherein the solid electrolyte lithium titanium aluminum phosphate precursor includes lithium, aluminum, titanium, oxygen, hydrogen and phosphorus.

[0015] In the XRD spectrum of the solid electrolyte lithium aluminum titanium phosphate precursor, the peak intensity ratio of the first strong diffraction peak and the second strong diffraction peak is 0.5-2.0, and the half-width range of the first strong diffraction peak and the second strong diffraction peak is independently 0.3-0.8°.

[0016] The peak position of the first strongest diffraction peak is in the range of 26.5-27.5°, and the peak position of the second strongest diffraction peak is in the range of 27.5-28.5°.

[0017] The solid electrolyte lithium titanium aluminum phosphate precursor of the present invention contains Li, Al, Ti, O, H and P elements, and in its XRD spectrum, the peak intensity ratio and half-height width of the first strong diffraction peak and the second strong diffraction peak are within a specific range, and it is a new material different from LATP; and the solid electrolyte lithium titanium aluminum phosphate precursor of the present invention only needs simple calcination to be converted into nano lithium titanium aluminum phosphate, and the size of the generated solid electrolyte lithium titanium aluminum phosphate precursor can be controlled within 30nm to several hundred nm according to the calcination conditions; at the same time, the solid electrolyte lithium titanium aluminum phosphate precursor of the present invention can be directly used for coating positive electrode materials, and a positive electrode material with a thin coating layer can be obtained after calcination.

[0018] The half-height width mentioned in the present invention refers to the peak width at half the peak height.

[0019] The peak intensity ratio of the first strong diffraction peak to the second strong diffraction peak is 0.5-2.0, for example, it can be 0.5, 0.7, 0.9, 1.1, 1.3, 1.5, 1.7 or 2.0, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0020] The half-widths of the first strong diffraction peak and the second strong diffraction peak are independently in the range of 0.3 to 0.8°, for example, 0.3°, 0.4°, 0.5°, 0.6°, 0.7° or 0.8°, but are not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0021] The peak position of the first strong diffraction peak is in the range of 26.5~27.5°, for example, it can be 26.5°, 26.7°, 26.9°, 27.1°, 27.3° or 27.5°; the peak position of the second strong diffraction peak is in the range of 27.5~28.5°, for example, it can be 27.5°, 27.7°, 27.9°, 28.1°, 28.3° or 28.5°, but is not limited to the listed values, and other unlisted values ​​within the numerical range are equally applicable.

[0022] Preferably, the primary particle size of the solid electrolyte lithium aluminum titanium phosphate precursor is 5 to 30 nm, for example, 5 nm, 10 nm, 15 nm, 20 nm, 25 nm or 30 nm, and the specific surface area is 60 to 150 m 2 / g, for example, it can be 60m 2 / g, 70m 2 / g, 80m 2 / g, 90m 2 / g、100m 2 / g, 110m 2 / g, 120m 2 / g, 130m 2 / g, 140m 2 / g or 150m 2 / g, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0023] The solid electrolyte lithium titanium aluminum phosphate precursor of the present invention has a small particle size, uniform size distribution, and is easy to disperse. It only needs to be simply calcined to be converted into nano lithium titanium aluminum phosphate. The size of the generated lithium titanium aluminum phosphate particles can be controlled between 30 nm and several hundred nm according to the calcination conditions. The obtained lithium titanium aluminum phosphate particles can be used as nano solid electrolyte materials for solid or semi-solid lithium ion batteries, or for coating positive electrode materials, ceramic diaphragm coating, and polymer-oxide composite solid electrolyte materials.

[0024] Preferably, in the solid electrolyte lithium titanium aluminum phosphate precursor, the molar ratio of lithium, aluminum, titanium and phosphorus is (1+x):x:(2-x):3, wherein x is 0~0.5, but does not include 0, for example, it can be 0.1, 0.2, 0.3, 0.4 or 0.5, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0025] Preferably, in the XRD spectrum of the solid electrolyte lithium aluminum titanium phosphate precursor, there are diffraction peaks at 2θ of 16.8~17.3°, for example, 16.8°, 17.0°, 17.2° or 17.3°; 18.3~18.9°, for example, 18.3°, 18.5°, 18.7° or 18.9°; 24.5~25.0°, for example, 24.5°, 24.7°, 24.9° or 25.0°.

[0026] In the XRD spectrum of the solid electrolyte lithium aluminum titanium phosphate precursor of the present invention, there are three weaker diffraction peaks at 2θ of 16.8-17.3°, 18.3-18.9° and 24.5-25.0°, respectively.

[0027] In a second aspect, the present invention provides a method for preparing the solid electrolyte lithium aluminum titanium phosphate precursor as described in the first aspect, the preparation method comprising the following steps:

[0028] (1) mixing a titanium source, an aluminum source, water and phosphoric acid to obtain a gel-like substance, and washing and drying the gel-like substance to obtain a solid substance;

[0029] (2) The solid substance, lithium source and water in step (1) are mixed and subjected to hydrothermal reaction to obtain a hydrothermal product, and the hydrothermal product is washed and dried to obtain the solid electrolyte lithium aluminum titanium phosphate precursor.

[0030] The present invention reacts a titanium source, an aluminum source solution and phosphoric acid to form a semisolid gel, which can achieve uniform mixing of Ti / Al / P and obtain a highly dispersed Ti / Al / P mixture. After fully mixing the washed and dried white solid substance with a lithium source-containing aqueous solution, a hydrothermal reaction is performed to obtain an ultrafine lithium aluminum titanium phosphate precursor with good crystallinity and a particle size of 5 to 30 nm.

[0031] The present invention does not use an organic solvent and directly uses phosphoric acid for reaction, thereby avoiding the generation of organic waste liquid and ammonia nitrogen waste water and the like.

[0032] Preferably, the mixing in step (1) comprises first mixing a titanium source, an aluminum source and water to obtain a mixed source solution, and then mixing the mixed source solution with phosphoric acid.

[0033] Preferably, in the mixed source solution, the total metal ion molar concentration is 1-3 mol / L, for example, 1 mol / L, 1.5 mol / L, 2 mol / L, 2.5 mol / L or 3 mol / L, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0034] In the mixed source solution when the titanium source and aluminum source react with phosphoric acid as described in the present invention, the total metal ion molar concentration will affect the washing efficiency of the Ti / Al / P mixture, and will also affect the particle size, morphology and phase structure of the product. If the total metal ion molar concentration of titanium and aluminum is too large, the powder particle size will be larger, the morphology structure will be denser, and the degree of crystallization will be too high; if the total metal ion molar concentration of titanium and aluminum is too small, the amount of deionized water used will be too much, which will increase the washing treatment time and reduce production efficiency.

[0035] Preferably, the mass concentration of the phosphoric acid is 30-85wt%, for example, 30wt%, 40wt%, 50wt%, 60wt%, 70wt%, 80wt% or 85wt%, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0036] Preferably, the titanium source in step (1) comprises titanium tetrachloride.

[0037] Preferably, the aluminum source in step (1) includes aluminum chloride hexahydrate and / or aluminum hydroxide.

[0038] All raw materials of the present invention do not use organic matter, but are inorganic salts or inorganic acids that can be obtained at low cost, and have no ammonia nitrogen emissions, which effectively saves costs, is safe and environmentally friendly, and can facilitate industrial production.

[0039] Preferably, the temperature of the hydrothermal reaction in step (2) is 130-200°C, for example, 130°C, 150°C, 170°C, 190°C or 200°C, and the time is 6-24h, for example, 6h, 10h, 14h, 18h, 22h or 24h, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0040] The temperature of the hydrothermal reaction described in the present invention will affect the size, morphology, phase composition and degree of crystallization of the product grains. If the hydrothermal reaction temperature is too low, the product morphology is a cluster structure composed of nano-flake particles, the phase composition remains unchanged or more impurities appear, and the crystallization is poor; if the hydrothermal reaction temperature is too high, the product particle size increases and impurities may appear.

[0041] Preferably, in the hydrothermal reaction system of step (2), the molar ratio of lithium, aluminum, titanium and phosphorus is (1+x)~(2+x):x:(2-x):3, for example, it can be (1+x):x:(2-x):3 or (2+x):x:(2-x):3, wherein x is 0~0.5, but does not include 0, for example, it can be 0.1, 0.2, 0.3, 0.4 or 0.5, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0042] Preferably, the mixing in step (2) comprises first mixing the lithium source and water to obtain a lithium source solution, and then mixing the lithium source solution with a solid substance.

[0043] Preferably, the mass concentration of the lithium source solution is 40-200 g / L, for example, 40 g / L, 100 g / L, 150 g / L or 200 g / L, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0044] The mass concentration of the lithium source solution during the hydrothermal reaction of the present invention will affect the yield of the hydrothermal product, the particle size of the powder and the degree of crystallization. If the mass concentration is too low, the yield of the hydrothermal product is low and the crystallinity is low; if the mass concentration is too high, the powder particle size is easy to grow.

[0045] Preferably, the lithium source in step (2) comprises lithium hydroxide monohydrate.

[0046] In a third aspect, the present invention provides a solid electrolyte lithium titanium aluminum phosphate, which is obtained by calcining the solid electrolyte lithium titanium aluminum phosphate precursor as described in the first aspect.

[0047] Preferably, the calcination temperature is 400-900°C, for example, it can be 400°C, 450°C, 500°C, 550°C, 600°C, 650°C, 700°C, 750°C, 800°C, 850°C or 900°C, preferably 750-900°C, and the time is 1-4h, for example, it can be 1h, 2h, 3h or 4h, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0048] According to the control of conditions, the present invention can prepare a porous structure formed by the adhesion of pure phase lithium titanium aluminum phosphate nanoparticles with a particle size of 30nm to several hundred nm, and then the calcined product is subjected to a certain grinding to obtain lithium titanium aluminum phosphate particles with a high dispersion of 30nm to several hundred nm, such as lithium titanium aluminum phosphate with a primary particle size of less than 100nm.

[0049] When the solid electrolyte lithium titanium aluminum phosphate precursor of the present invention is calcined to prepare the solid electrolyte lithium titanium aluminum phosphate, if the calcination temperature is too low, the obtained product phase is impure, and if the temperature is too high, the particles grow too large.

[0050] In a fourth aspect, the present invention provides a positive electrode material, the surface of which is coated with a coating layer, and the positive electrode material is obtained by mixing and sintering the solid electrolyte lithium aluminum titanium phosphate precursor as described in the first aspect with an uncoated positive electrode material.

[0051] The present invention directly uses a solid electrolyte lithium titanium aluminum phosphate precursor for coating, which can obtain a thinner and more uniform coating layer; and the surface coating layer of the positive electrode material contains Li element, Al element, Ti element and phosphate, etc. Since lithium titanium aluminum phosphate may react with the surface of the positive electrode material during sintering, the substance finally coated on the surface is not necessarily lithium titanium aluminum phosphate.

[0052] Preferably, the thickness of the coating layer on the surface of the positive electrode material is less than 10 nm, for example, it can be 9 nm, 8 nm, 7 nm, 6 nm or 5 nm, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0053] Preferably, the solid electrolyte lithium titanium aluminum phosphate precursor accounts for 0.1-0.5wt% of the total mass of the solid electrolyte lithium titanium aluminum phosphate precursor and the uncoated positive electrode material, for example, it can be 0.1wt%, 0.2wt%, 0.3wt%, 0.4wt% or 0.5wt%, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0054] Preferably, the sintering temperature is 400-900°C, for example, 400°C, 600°C, 800°C or 900°C, and the sintering time is 1-4h, for example, 1h, 2h, 3h or 4h, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0055] Preferably, the positive electrode material includes any one of lithium cobalt oxide, spinel lithium manganese oxide, ternary materials or nickel cobalt lithium manganese oxide with an average particle size greater than 2 μm, or a combination of at least two thereof.

[0056] Compared with the prior art, the present invention has the following beneficial effects:

[0057] (1) The present invention uses a mixed salt solution of a titanium source such as titanium tetrachloride and an aluminum source to react with phosphoric acid to form a semi-solid gel, which can achieve uniform mixing of Ti / Al / P and obtain a highly dispersed Ti / Al / P mixture. After the washed and dried white substance is fully mixed with a lithium source aqueous solution, a hydrothermal reaction is carried out at a certain temperature for a certain period of time to obtain an ultrafine lithium aluminum titanium phosphate precursor with good crystallinity and a particle size of 5 to 30 nm;

[0058] (2) The present invention can mix the ultrafine lithium titanium aluminum phosphate precursor with the positive electrode material of the lithium ion battery through a dry or wet coating process to form a coating layer on the surface of the positive electrode, and then simply calcine to obtain a positive electrode material with a lithium titanium aluminum phosphate coating layer having a coating thickness of less than 10nm. The thin layer coating can stabilize the structure of the positive electrode material, reduce the side reactions at the positive electrode / electrolyte interface, and improve the performance of the lithium ion battery while ensuring the original performance of the battery;

[0059] (3) The present invention obtains high-purity solid electrolyte lithium titanium aluminum phosphate by calcining ultrafine lithium titanium aluminum phosphate precursor particles. By controlling the calcination temperature and time, lithium titanium aluminum phosphate particles with different particle sizes can be obtained, which can be applied to different scenarios such as surface coating of lithium ion battery positive electrode materials, addition of positive electrode slurry, and preparation of solid-state lithium ion batteries;

[0060] (4) The preparation method of the solid electrolyte lithium aluminum titanium phosphate precursor of the present invention does not use organic matter, does not introduce ammonia nitrogen, does not contain strong oxidants, the raw materials are simple and easy to obtain, the preparation method is controllable and easy to operate, and the reaction conditions are mild, which can realize industrial production;

[0061] (5) The preparation method of the present invention facilitates the formulation adjustment and doping of lithium aluminum titanium phosphate to further optimize the performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0062] Figure 1 This is the XRD pattern of the solid electrolyte lithium aluminum titanium phosphate precursor obtained in Example 1 of the present invention;

[0063] Figure 2 This is a SEM image of the solid electrolyte lithium aluminum titanium phosphate precursor obtained in Example 1 of the present invention at a scale of 2 μm;

[0064] Figure 3 This is a SEM image of the solid electrolyte lithium aluminum titanium phosphate precursor obtained in Example 1 of the present invention at a scale of 1 μm;

[0065] Figure 4 This is a particle size distribution diagram of the solid electrolyte lithium aluminum titanium phosphate precursor obtained in Example 1 of the present invention;

[0066] Figure 5 This is a SEM image at a scale of 2 μm after the solid electrolyte lithium aluminum titanium phosphate precursor obtained in Example 1 of the present invention is used as a coating material to coat the positive electrode material;

[0067] Figure 6 This is a SEM image at a scale of 1 μm after the solid electrolyte lithium aluminum titanium phosphate precursor obtained in Example 1 of the present invention is used as a coating material to coat the positive electrode material;

[0068] Figure 7 This is a SEM image of the solid electrolyte lithium aluminum titanium phosphate obtained after the solid electrolyte lithium aluminum titanium phosphate precursor obtained in Example 1 of the present invention is calcined at 800° C. for 2 hours;

[0069] Figure 8 This is a SEM image of the solid electrolyte lithium aluminum titanium phosphate obtained after the solid electrolyte lithium aluminum titanium phosphate precursor obtained in Example 1 of the present invention is calcined at 900° C. for 2 hours;

[0070] Fig. 9This is a thermogravimetric diagram of the solid electrolyte lithium aluminum titanium phosphate precursor obtained in Example 1 of the present invention;

[0071] Fig.10 This is an infrared image of the solid electrolyte lithium aluminum titanium phosphate precursor obtained in Example 1 of the present invention;

[0072] Fig.11 This is a SEM image of the solid electrolyte lithium aluminum titanium phosphate precursor obtained in Example 4 of the present invention;

[0073] Fig.12 This is the XRD pattern of the solid electrolyte lithium aluminum titanium phosphate precursor obtained in Example 4 of the present invention;

[0074] Fig.13 This is a SEM image of the solid electrolyte lithium aluminum titanium phosphate precursor obtained in Example 5 of the present invention;

[0075] Fig.14 This is the XRD pattern of the solid electrolyte lithium aluminum titanium phosphate precursor obtained in Example 5 of the present invention;

[0076] Fig.15 This is a SEM image of the solid electrolyte lithium aluminum titanium phosphate precursor obtained in Example 6 of the present invention;

[0077] Fig.16 This is a SEM image of the solid electrolyte lithium aluminum titanium phosphate precursor obtained in Example 10 of the present invention;

[0078] Fig.17 This is an XRD pattern of the solid electrolyte lithium aluminum titanium phosphate precursor obtained in Example 10 of the present invention;

[0079] Fig.18 This is the XRD pattern of the solid electrolyte lithium aluminum titanium phosphate obtained in Example 1 of the present invention;

[0080] Fig.19 These are the XRD patterns of the solid electrolyte lithium aluminum titanium phosphate precursor, the solid electrolyte lithium aluminum titanium phosphate and the standard XRD patterns of lithium aluminum titanium phosphate obtained in Example 1 of the present invention. DETAILED DESCRIPTION

[0081] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0082] Example 1

[0083] This embodiment provides a solid electrolyte lithium titanium aluminum phosphate precursor, the solid electrolyte lithium titanium aluminum phosphate precursor includes lithium, aluminum, titanium and phosphorus in a molar ratio of 1.3:0.3:1.7:3, and the XRD pattern of the solid electrolyte lithium titanium aluminum phosphate precursor is as follows: Figure 1 As shown, there are a first strong characteristic diffraction peak and a second strong characteristic diffraction peak in the XRD spectrum, and there are three weaker characteristic diffraction peaks at 17.1°, 18.6°, and 24.8°.

[0084] The SEM image of the solid electrolyte lithium aluminum titanium phosphate precursor obtained in this example at a scale of 2 μm is as follows: Figure 2 As shown, the SEM image at 1 μm scale is Figure 3 The particle size distribution diagram is shown in Figure 4 As shown by Figure 2-Figure 4 It can be seen that the particle size of the solid electrolyte lithium aluminum titanium phosphate precursor obtained in this embodiment is relatively small, which can reach 5~30nm.

[0085] The thermogravimetric diagram of the solid electrolyte lithium aluminum titanium phosphate precursor obtained in this example is as follows Fig. 9 As shown in Figure 2, the ignition loss of the solid electrolyte lithium aluminum titanium phosphate precursor at 820 ° C is between 3% and 13.58%, which is Fig. 9 It can be seen that when the lithium aluminum titanium phosphate precursor is subjected to thermogravimetric testing in an air atmosphere, the mass gradually decreases when the temperature rises from 30°C to about 400°C. When the temperature continues to rise to 650°C, the mass fluctuates but maintains an overall downward trend, and then begins to stabilize.

[0086] The infrared image of the solid electrolyte lithium aluminum titanium phosphate precursor obtained in this example is as follows Fig.10 As shown, at 3396cm -1 1654cm -1 The -OH absorption peak at may come from adsorbed water or crystallized water. Combined with the loss on ignition and thermogravimetric data, it is speculated that the lithium aluminum titanium phosphate precursor may contain a certain amount of crystallized water.

[0087] The preparation method of the solid electrolyte lithium aluminum titanium phosphate precursor comprises the following steps:

[0088] Lithium hydroxide monohydrate, aluminum chloride hexahydrate, titanium tetrachloride and phosphoric acid were weighed according to the molar ratio of Li:Al:Ti:P=1.43:0.3:1.7:3, wherein the mass concentration of phosphoric acid was 85%, and aluminum chloride hexahydrate and titanium tetrachloride were prepared into an aluminum-titanium mixed salt solution with a total molar concentration of 1.6 mol / L. The aluminum-titanium mixed salt solution was mixed with phosphoric acid to form a semisolid gel, and the obtained gel was washed with deionized water and filtered repeatedly until neutral, and placed in a blast oven and dried at 90°C to obtain a white solid. Lithium hydroxide monohydrate was prepared into a lithium hydroxide solution with a mass concentration of 80 g / L, the white solid was ground and mixed with the lithium hydroxide solution, and transferred to a 250 ml sealed reactor, and hydrothermally reacted at 130°C for 18 hours. After the reaction was completed, the hydrothermal product was taken out after the reactor was cooled to room temperature, washed with deionized water until neutral, and dried at 90°C to obtain a lithium aluminum phosphate precursor.

[0089] This embodiment also provides a positive electrode material coated with lithium aluminum titanium phosphate, and the preparation method of the positive electrode material comprises the following steps:

[0090] The lithium cobalt oxide powder was placed in a special mixing tank of a high-speed mixer, and lithium aluminum titanium phosphate precursor powder accounting for 1% of the total mass percentage of lithium cobalt oxide and lithium aluminum titanium phosphate precursor was added, and high-speed mixing was performed at a speed of 2000 rpm and a mixing time of 3 min to obtain a dry mixture. The dry mixture was calcined at 800° C. for 2 h to obtain lithium cobalt oxide coated with lithium aluminum titanium phosphate. The SEM image of the solid electrolyte lithium aluminum titanium phosphate precursor obtained in this embodiment after coating the positive electrode material as a coating material is as follows: Figure 5 As shown, the SEM image at 1 μm scale is Figure 6 shown.

[0091] This embodiment also provides a solid electrolyte lithium titanium aluminum phosphate, and the preparation method of the solid electrolyte lithium titanium aluminum phosphate comprises the following steps:

[0092] The solid electrolyte lithium aluminum titanium phosphate precursor described in this example was calcined at 800° C. for 2 h to obtain a SEM image as shown in FIG. Figure 7 The solid electrolyte lithium aluminum titanium phosphate shown in FIG. Fig.18 As shown, the XRD patterns of the solid electrolyte lithium aluminum titanium phosphate precursor, the solid electrolyte lithium aluminum titanium phosphate and the standard XRD patterns of lithium aluminum titanium phosphate obtained in this embodiment are as shown in Fig.19 As shown by Fig.19 It can be seen that the diffraction peak positions of the solid electrolyte lithium titanium aluminum phosphate precursor and the solid electrolyte lithium titanium aluminum phosphate are different. After calcining the solid electrolyte lithium titanium aluminum phosphate precursor of the present invention, a solid electrolyte lithium titanium aluminum phosphate corresponding to the standard spectrum can be obtained.

[0093] When the solid electrolyte lithium aluminum titanium phosphate precursor described in this embodiment is calcined at 900° C. for 2 h, the SEM image of the obtained solid electrolyte lithium aluminum titanium phosphate is as follows: Figure 8 As shown by Figure 7 and Figure 8 It can be seen that the use of lithium titanium aluminum phosphate precursor as the surface coating material of the positive electrode is conducive to achieving a thin and uniform coating on the positive electrode surface due to its small particle size, uniform particle size and easy dispersion. The amount used is more advantageous than using lithium titanium aluminum phosphate nanoparticles with larger particle size obtained after calcination for coating.

[0094] Example 2

[0095] The present embodiment provides a solid electrolyte lithium titanium aluminum phosphate precursor, which includes lithium, aluminum, titanium and phosphorus in a molar ratio of 1.5:0.5:1.5:3. The XRD spectrum of the solid electrolyte lithium titanium aluminum phosphate precursor has a first strong characteristic diffraction peak and a second strong characteristic diffraction peak, and three weaker characteristic diffraction peaks at 16.8°, 18.3° and 24.5°.

[0096] The preparation method of the solid electrolyte lithium aluminum titanium phosphate precursor comprises the following steps:

[0097] According to the molar ratio of Li:Al:Ti:P=2:0.5:1.5:3, lithium hydroxide monohydrate, aluminum chloride hexahydrate, titanium tetrachloride and phosphoric acid are weighed, wherein the mass concentration of phosphoric acid is 30wt%, and aluminum chloride hexahydrate and titanium tetrachloride are prepared into an aluminum-titanium mixed salt solution with a total molar concentration of 1mol / L. The aluminum-titanium mixed salt solution is mixed with phosphoric acid to form a semisolid gel, and the obtained gel is washed with deionized water and filtered repeatedly until neutral, and placed in a blast oven and dried at 90°C to obtain a white solid. Lithium hydroxide monohydrate is prepared into a lithium hydroxide solution with a mass concentration of 40g / L, the white solid is ground and mixed with the lithium hydroxide solution, transferred to a 250ml sealed reactor, and hydrothermally reacted at 130°C for 24h. After the reaction is completed, the hydrothermal product is taken out after the reactor is cooled to room temperature, washed with deionized water until neutral, and dried at 90°C to obtain a lithium aluminum phosphate precursor.

[0098] This embodiment also provides a solid electrolyte lithium titanium aluminum phosphate, and the preparation method of the solid electrolyte lithium titanium aluminum phosphate comprises the following steps:

[0099] The solid electrolyte lithium aluminum titanium phosphate precursor described in this embodiment is calcined at 750° C. for 4 hours to obtain the solid electrolyte lithium aluminum titanium phosphate.

[0100] Example 3

[0101] The present embodiment provides a solid electrolyte lithium titanium aluminum phosphate precursor, which includes lithium, aluminum, titanium and phosphorus in a molar ratio of 1.1:0.1:1.9:3. The XRD spectrum of the solid electrolyte lithium titanium aluminum phosphate precursor has a first strong characteristic diffraction peak and a second strong characteristic diffraction peak, and three weaker characteristic diffraction peaks at 17.3°, 18.9° and 25.0°.

[0102] The preparation method of the solid electrolyte lithium aluminum titanium phosphate precursor comprises the following steps:

[0103] Lithium hydroxide monohydrate, aluminum chloride hexahydrate, titanium tetrachloride and phosphoric acid were weighed according to the molar ratio of Li:Al:Ti:P=1.1:0.1:1.9:3, wherein the mass concentration of phosphoric acid was 50wt%, and aluminum chloride hexahydrate and titanium tetrachloride were prepared into an aluminum-titanium mixed salt solution with a total molar concentration of 3mol / L. The aluminum-titanium mixed salt solution was mixed with phosphoric acid to form a semisolid gel, and the obtained gel was washed with deionized water and filtered repeatedly until neutral, and placed in a blast oven and dried at 90°C to obtain a white solid. Lithium hydroxide monohydrate was prepared into a lithium hydroxide solution with a mass concentration of 200g / L, the white solid was ground and mixed with the lithium hydroxide solution, and transferred to a 250ml sealed reactor, and hydrothermally reacted at 200°C for 6h. After the reaction was completed, the hydrothermal product was taken out after the reactor was cooled to room temperature, washed with deionized water until neutral, and dried at 90°C to obtain a lithium aluminum phosphate precursor.

[0104] This embodiment also provides a solid electrolyte lithium titanium aluminum phosphate, and the preparation method of the solid electrolyte lithium titanium aluminum phosphate comprises the following steps:

[0105] The solid electrolyte lithium aluminum titanium phosphate precursor described in this embodiment was calcined at 900° C. for 1 hour to obtain the solid electrolyte lithium aluminum titanium phosphate.

[0106] Example 4

[0107] The present embodiment provides a solid electrolyte lithium titanium aluminum phosphate precursor, which is the same as that of Embodiment 1 except that in its preparation method, the temperature of the hydrothermal reaction is 150° C., so that the obtained solid electrolyte lithium titanium aluminum phosphate precursor has adaptability changes.

[0108] The SEM image of the solid electrolyte lithium aluminum titanium phosphate precursor obtained in this example is as follows: Fig.11 As shown, the XRD pattern is Fig.12 shown.

[0109] This embodiment also provides a solid electrolyte lithium titanium aluminum phosphate, and the preparation method of the solid electrolyte lithium titanium aluminum phosphate comprises the following steps:

[0110] The solid electrolyte lithium aluminum titanium phosphate precursor described in this embodiment is calcined at 800° C. for 2 hours to obtain the solid electrolyte lithium aluminum titanium phosphate.

[0111] Example 5

[0112] The present embodiment provides a solid electrolyte lithium titanium aluminum phosphate precursor, which is the same as Example 1 except that in its preparation method, the temperature of the hydrothermal reaction is 150° C., and the mass concentration of the lithium hydroxide solution is 160 g / L, so that the obtained solid electrolyte lithium titanium aluminum phosphate precursor has adaptability changes.

[0113] The SEM image of the solid electrolyte lithium aluminum titanium phosphate precursor obtained in this example is as follows: Fig.13 As shown, the XRD pattern is Fig.14 shown.

[0114] This embodiment also provides a solid electrolyte lithium titanium aluminum phosphate, and the preparation method of the solid electrolyte lithium titanium aluminum phosphate comprises the following steps:

[0115] The solid electrolyte lithium aluminum titanium phosphate precursor described in this embodiment is calcined at 800° C. for 2 hours to obtain the solid electrolyte lithium aluminum titanium phosphate.

[0116] Example 6

[0117] The present embodiment provides a solid electrolyte lithium aluminum titanium phosphate precursor, which is the same as Example 1 except that in its preparation method, the concentration of the aluminum-titanium mixed salt solution is 2.4 mol / L, so that the obtained solid electrolyte lithium aluminum titanium phosphate precursor has adaptability changes.

[0118] The SEM image of the solid electrolyte lithium aluminum titanium phosphate precursor obtained in this example is as follows: Fig.15 shown.

[0119] This embodiment also provides a solid electrolyte lithium titanium aluminum phosphate, and the preparation method of the solid electrolyte lithium titanium aluminum phosphate comprises the following steps:

[0120] The solid electrolyte lithium aluminum titanium phosphate precursor described in this embodiment is calcined at 800° C. for 2 hours to obtain the solid electrolyte lithium aluminum titanium phosphate.

[0121] Example 7

[0122] The present embodiment provides a solid electrolyte lithium aluminum titanium phosphate precursor, which is the same as Example 1 except that in its preparation method, the concentration of the aluminum-titanium mixed salt solution is 0.5 mol / L, so that the obtained solid electrolyte lithium aluminum titanium phosphate precursor has adaptability changes.

[0123] This embodiment also provides a solid electrolyte lithium titanium aluminum phosphate, and the preparation method of the solid electrolyte lithium titanium aluminum phosphate comprises the following steps:

[0124] The solid electrolyte lithium aluminum titanium phosphate precursor described in this embodiment is calcined at 800° C. for 2 hours to obtain the solid electrolyte lithium aluminum titanium phosphate.

[0125] Example 8

[0126] The present embodiment provides a solid electrolyte lithium aluminum titanium phosphate precursor, which is the same as Example 1 except that in its preparation method, the concentration of the aluminum-titanium mixed salt solution is 3.5 mol / L, so that the obtained solid electrolyte lithium aluminum titanium phosphate precursor has adaptability changes.

[0127] This embodiment also provides a solid electrolyte lithium titanium aluminum phosphate, and the preparation method of the solid electrolyte lithium titanium aluminum phosphate comprises the following steps:

[0128] The solid electrolyte lithium aluminum titanium phosphate precursor described in this embodiment is calcined at 800° C. for 2 hours to obtain the solid electrolyte lithium aluminum titanium phosphate.

[0129] Example 9

[0130] The present embodiment provides a solid electrolyte lithium titanium aluminum phosphate precursor, which is the same as Example 1 except that in its preparation method, the temperature of the hydrothermal reaction is 220° C., so that the obtained solid electrolyte lithium titanium aluminum phosphate precursor has adaptability changes.

[0131] This embodiment also provides a solid electrolyte lithium titanium aluminum phosphate, and the preparation method of the solid electrolyte lithium titanium aluminum phosphate comprises the following steps:

[0132] The solid electrolyte lithium aluminum titanium phosphate precursor described in this embodiment is calcined at 800° C. for 2 hours to obtain the solid electrolyte lithium aluminum titanium phosphate.

[0133] Example 10

[0134] The present embodiment provides a solid electrolyte lithium titanium aluminum phosphate precursor, which is the same as Example 1 except that in its preparation method, the temperature of the hydrothermal reaction is 120° C. to make the obtained solid electrolyte lithium titanium aluminum phosphate precursor adaptable.

[0135] The SEM image of the solid electrolyte lithium aluminum titanium phosphate precursor obtained in this example is as follows: Fig.16 As shown, the XRD pattern is Fig.17 shown.

[0136] This embodiment also provides a solid electrolyte lithium titanium aluminum phosphate, and the preparation method of the solid electrolyte lithium titanium aluminum phosphate comprises the following steps:

[0137] The solid electrolyte lithium aluminum titanium phosphate precursor described in this embodiment is calcined at 800° C. for 2 hours to obtain the solid electrolyte lithium aluminum titanium phosphate.

[0138] Embodiment 11

[0139] This embodiment provides a solid electrolyte lithium titanium aluminum phosphate precursor, and the solid electrolyte lithium titanium aluminum phosphate precursor and its preparation method are the same as those in Example 1.

[0140] This embodiment further provides a solid electrolyte lithium aluminum titanium phosphate. The preparation method of the solid electrolyte lithium aluminum titanium phosphate is the same as that of Embodiment 1 except that the calcination temperature is 650°C.

[0141] Example 12

[0142] This embodiment provides a solid electrolyte lithium titanium aluminum phosphate precursor, and the solid electrolyte lithium titanium aluminum phosphate precursor and its preparation method are the same as those in Example 1.

[0143] This embodiment also provides a solid electrolyte lithium aluminum titanium phosphate. The preparation method of the solid electrolyte lithium aluminum titanium phosphate is the same as that of Embodiment 1 except that the calcination temperature is 1000° C.

[0144] Comparative Example 1

[0145] This comparative example provides a solid electrolyte lithium aluminum titanium phosphate precursor. The preparation method of the solid electrolyte lithium aluminum titanium phosphate precursor is the same as Example 1, except that a lithium hydroxide solution is mixed with an aluminum-titanium mixed brine solution and phosphoric acid and then subjected to a hydrothermal reaction to make the obtained solid electrolyte lithium aluminum titanium phosphate precursor adaptable.

[0146] In the XRD spectra of the solid electrolyte lithium aluminum titanium phosphate precursor obtained in the above embodiments and comparative examples, the peak positions, peak intensity ratios and half-widths of the first strong diffraction peak and the second strong diffraction peak, the primary particle size range of the solid electrolyte lithium aluminum titanium phosphate precursor, and the primary particle size range of the obtained solid electrolyte lithium aluminum titanium phosphate are shown in Table 1.

[0147] Table 1

[0148]

[0149] From Table 1 we can see that:

[0150] It can be seen from Examples 1-3 and Comparative Example 1 that the present invention uses a mixed salt solution of titanium tetrachloride and an aluminum source to react with phosphoric acid, and then fully mixes with a lithium source aqueous solution and then hydrothermally reacts to obtain a lithium aluminum titanium phosphate precursor with good crystallinity and ultrafine particle size. In Comparative Example 1, the lithium source reacts with the titanium source, the aluminum source and phosphoric acid together, and then hydrothermally reacts, which will cause the particle size of the lithium aluminum titanium phosphate precursor to be larger; from Examples 1 and 4-10, combined with Figure 11-Figure 16It can be seen that the temperature of the hydrothermal reaction, the mass concentration of the lithium hydroxide solution and the concentration of the aluminum-titanium mixed salt solution of the present invention will affect the particle size of the primary particles of the product, especially the temperature of the hydrothermal reaction, which will have a greater impact on the particle size of the lithium aluminum titanium phosphate precursor; it can be seen from Example 1 and Examples 11-12 that when the solid electrolyte lithium aluminum titanium phosphate precursor is used to prepare the solid electrolyte lithium aluminum titanium phosphate, if the temperature is not within the preferred range, it will affect the purity or particle size of the obtained solid electrolyte lithium aluminum titanium phosphate.

[0151] In summary, the present invention provides a solid electrolyte lithium titanium aluminum phosphate precursor and its preparation method and application. The preparation method can prepare lithium titanium aluminum phosphate precursor particles with a primary particle size of 5 to 30 nm. The precursor particles only need simple calcination to be converted into nano lithium titanium aluminum phosphate, or can be used for coating of positive electrode materials, ceramic diaphragm coating and polymer-oxide composite solid electrolyte materials.

[0152] The above description is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention are within the protection scope and disclosure scope of the present invention.

Claims

1. A solid electrolyte lithium aluminum titanium phosphate precursor, characterized in that: The solid electrolyte lithium aluminum titanium phosphate precursor includes lithium, aluminum, titanium, oxygen, hydrogen and phosphorus; In the XRD spectrum of the solid electrolyte lithium aluminum titanium phosphate precursor, the peak intensity ratio of the first strong diffraction peak and the second strong diffraction peak is 0.5-2.0, and the half-width range of the first strong diffraction peak and the second strong diffraction peak is independently 0.3-0.8°; The peak position of the first strongest diffraction peak is in the range of 26.5-27.5°, and the peak position of the second strongest diffraction peak is in the range of 27.5-28.5°; The primary particle size of the solid electrolyte lithium aluminum titanium phosphate precursor is 5-30 nm.

2. The solid electrolyte lithium aluminum titanium phosphate precursor according to claim 1, characterized in that The specific surface area of ​​the solid electrolyte lithium aluminum titanium phosphate precursor is 60-150 m 2 / g; In the solid electrolyte lithium aluminum titanium phosphate precursor, the molar ratio of lithium, aluminum, titanium and phosphorus is (1+x):x:(2-x):3, wherein x is 0 to 0.5, but does not include 0; In the XRD spectrum of the solid electrolyte lithium aluminum titanium phosphate precursor, diffraction peaks also exist at 2θ of 16.8-17.3°, 18.3-18.9° and 24.5-25.0°.

3. A method for preparing a solid electrolyte lithium aluminum titanium phosphate precursor as claimed in claim 1 or 2, characterized in that: The preparation method comprises the following steps: (1) mixing a titanium source, an aluminum source, water and phosphoric acid to obtain a gel-like substance, and washing and drying the gel-like substance to obtain a solid substance; The mixing includes first mixing a titanium source, an aluminum source and water to obtain a mixed source solution, and then mixing the mixed source solution with phosphoric acid; in the mixed source solution, the total metal ion molar concentration is 1-3 mol / L; (2) mixing the solid substance, lithium source and water in step (1) and subjecting them to a hydrothermal reaction to obtain a hydrothermal product, and washing and drying the hydrothermal product to obtain the solid electrolyte lithium aluminum titanium phosphate precursor; The temperature of the hydrothermal reaction is 130-200°C.

4. The preparation method according to claim 3, characterized in that: The mass concentration of the phosphoric acid is 30-85wt%.

5. The preparation method according to claim 3 or 4, characterized in that: The titanium source in step (1) comprises titanium tetrachloride; The aluminum source in step (1) includes aluminum chloride hexahydrate and / or aluminum hydroxide.

6. The preparation method according to claim 3 or 4, characterized in that: The hydrothermal reaction time in step (2) is 6 to 24 hours; In the hydrothermal reaction system of step (2), the molar ratio of lithium, aluminum, titanium and phosphorus is (1+x)~(2+x):x:(2-x):3, wherein x is 0~0.5, but excluding 0.

7. The preparation method according to claim 3 or 4, characterized in that: The mixing in step (2) comprises first mixing a lithium source and water to obtain a lithium source solution, and then mixing the lithium source solution with a solid substance; The mass concentration of the lithium source solution is 40-200 g / L.

8. A solid electrolyte lithium aluminum titanium phosphate, characterized in that: The solid electrolyte lithium titanium aluminum phosphate is obtained by calcining the solid electrolyte lithium titanium aluminum phosphate precursor as claimed in claim 1 or 2.

9. The solid electrolyte lithium aluminum titanium phosphate according to claim 8, characterized in that The calcination temperature is 400-900° C. and the calcination time is 1-4 hours.

10. A positive electrode material, characterized in that: The surface of the positive electrode material is coated with a coating layer, and the positive electrode material is obtained by mixing and sintering the solid electrolyte lithium aluminum titanium phosphate precursor as claimed in claim 1 or 2 with an uncoated positive electrode material.